Implementation of PI Controller for 4ф Srm Drive Using TMS320F28335 - Mekala N; Muniraj C (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents the experimental investigation of DSP based 4Ф Switched Reluctance Motor (SRM) Drive. SRM is a doubly-salient, singly-excited machine and having very simple construction, has a low inertia and allows an extremely high-speed operation. The control system of SRM is highly complex due to non linear nature. In such a system for implementing control algorithm needs high speed processor. In this work TMS320F28335 DSP processor is used to implement the inner loop PI current controller and outer loop PI speed controller. The TMS320F28335 is highly integrated, high performance solution for challenging control applications. The various experimental tests are carried out in 1 HP 4Ф SRM. The experimental results are reported in order to verify the steady state, transient and robustness performance of the controller.